FORMULASI PRODUK FLAKE SEREAL MENGGUNAKAN TEPUNG KACANG NAGARA TERMODIFIKASI Lactobacillus plantarum, TEPUNG BERAS HITAM DAN TEPUNG PISANG : VARIASI PROPORSI TEPUNG KOMPOSIT DAN LAMA STEAMING - Susi Susi, Lya Agustina, dan Udiantoro (Jurnal Teknologi Industri Pertanian, 2019)
The nagara beans fermented by lactic acid bacteria Lactobacillus plantarum have better physicochemical properties than unfermented beans, as well as protein and starch digestibility. Nagara bean flour that have been modified by L. plantarum can be used for the formulation of complementary food products in the form of breakfast cereals. Breakfast cereal products must contain enough nutrients, and have good acceptability.  The quality improvement of cereal flake products ca be done by making a composite of nagara bean flour with the addition of black rice flour which contains antioxidant compounds and banana flour which is able to support the digestibility of breakfast cereal produced.  This research was aimed to get the good breakfast cereal formulation and steaming periods where the product has high nutrition and sensory properties received. This study was conducted using a randomized block design, cereal flake formulation was carried out using nagara bean flour fermented by L. plantarum, banana flour and black rice flour with a proportion nagara bean flour of 0 to 100 percent and then steamed at a pressure of 80 kPa for 30 and 60 minutes. The results showed that the higher proportion of nagara beans in composite flour would decrease the acceptability but the dissolved protein content would increase with the increasing proportion of nagara bean flour. The proportion of nagara bean flour modified by L. plantarum up to 40 percent showed preference close rather like, with starch content ranging from 48.89–52.02% db, dissolved protein of 5.29-5.97 mg/mL, and resistant starch content of 1.84-2.90% db with average of in vitro starch digestibility of cereal flake was 87.60%.Keywords: nagara bean, L. plantarum, flake cereal, protein, resistent starch